Pengaruh Gaya Kepemimpinan Demokratis dan Budaya Organisasi terhadap Kinerja Karyawan pada Koperasi KPRI Teluk Mengkudu - Cia Cai Cen (Departement of Mathematics Education, 2023)
This study aims to determine the influence of Democratic Leadership Style and Organizational Culture on Employee Performance at Kpri Cooperative Teluk Mengkudu. The population in this study were employees of the KPRI Teluk Mengkudu Cooperative. In determining the sample used census technique, samples taken as many as 34 respondents. The analytical tool in this study used the SPSS 25.00 for Windows program. The research results show that: 1). It can be seen that the Democratic Leadership Style variable (X1) obtained tcount (0.919) < ttable (2.048), as well as with a significance value of 0.365> 0.05, it can be concluded that the first hypothesis is rejected, meaning that the Democratic Leadership Style Variable has no effect on the Performance Improvement Variable Employees, 2). It can be seen that the Organizational Culture variable (X2) obtained tcount (3.704) > ttable (2.048), and its significance value is 0.001 <0.05 so it can be concluded that the second hypothesis is accepted, meaning that Organizational Culture Variables affect employee Performance Variables, 3). It can be seen that Fcount (10.046) > Ftable (3.35), and a significance value of 0.000 <0.05, it can be concluded that the third hypothesis is accepted, meaning that the Democratic Leadership Style Variable and Organizational Culture Variable influence simultaneously (simultaneously) on the Variable Employee performance.